Persepsi Petani terhadap Teknologi Pengendalian Hama dan Penyakit Terpadu Padi Sawah dengan Agensia Hayati (Studi Kasus di Kelurahan Semarang Kota Bengkulu) - Alfayanti Alfayanti; Yesmawati Yesmawati; Linda Harta; Kusmea Dinata; Shannora Yuliasari (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Alfayanti A, Yesmawati Y, Harta L, Dinata K, Yuliasari S. 2021. Farmers perceptions on rice fields integrated pest control program with biological agents (case study in semarang village Bengkulu City). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 233-241. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Dissemination of integrated pest control program (IPM) technology with biological agents needs to be carried out so that farmers are willing to adopt it. One of the determinants of adoption is farmer's perception about nature of innovation technology. This study aims to identify farmers' perceptions about IPM technology with biological agents. The research was carried out in Semarang Urban Village Bengkulu City in May-July 2021 involving 32 farmers. The location was determined purposively because it is the location for biological IPM displays. The biological agents used were consortium of bacteria Paenibacillus polymixa, Pseudomonas flourescense, and Bacillus subtilis for disease control and consortium of fungi Metharihizium sp and Beuveria sp for pest control. The data measured is the farmer's perception of the nature of innovation technology using Likert scale and analyzed with quantitative descriptive method. Data were collected by conducting interviews using a questionnaire. The results showed that farmers assessed IPM technology with biological agents are accordance with cultural values, provides benefits, is easy to observe but is quite complicated to apply and try out.